Midtemperature solar systems test facility predictions for thermal performance based on test data: Sun-Heet nontracking solar collector - Harrison, T.D. (Sandia National Laboratories, 1981)
Sandia National Laboratories, Albuquerque (SNLA), is currently conducting a program to predict the performance and measure the characteristics of commercially available solar collectors that have the potential for use in industrial process heat and enhanced oil recovery applications. The thermal performance predictions for the Sun-Heet nontracking, line-focusing parabolic trough collector at five cities in the US are presented. (WHK)